Features of lexical verbs in the discussion section of masters' dissertations / Faizah Mohamad Nusri - Faizah , Mohamad Nusri (2018)
This study examines the use of lexical verbs in Discussion sections of Master’s Degree Dissertations submitted to the Faculty of Languages and Linguistics of University of Malaya. Lexical verbs are known to be prevalent in academic discourse notably in modulating writers’ ideas and stances to the readers. In order to convey their thoughts and communicate well with the readers, precise and succinct use of lexical verbs is paramount. Building on this background, the primary focus of the paper is an investigation of the use of lexical verbs in advanced ESL writing. Lexical verbs found in the academic texts are examined to identify the nature of verbal use and knowledge among advanced ESL speakers by the basis of types of lexical verbs, verb forms and associated verb patterns. It is interesting to note that Mental-Emotive verbs are second most commonly used verbs, after Activity verbs. The results also indicate the writers’ tendency to employ passive voice in their writing, which is generally avoided by ESL and non-native writers in other studies despite its conventionalized use in academic discourse. The key verb-based patterns examined in this paper are Passive+PP and V-that patterns in verb-based bundles. Passive voice is predominantly used in combination with PP in and by. This result indicates writers’ adherence to academic text objectivity and detachment conventions. Common V-that patterns examplify the writers’ confidence in their claims. Analysis of V-that pattern also show writers’ tendency to discriminate verb type according to animacy of the subject. This research highlights the use of accurate verb and importance of phraseological knowledge in academic writing and proposes analysis of academic verbs and common patterns as linguistic awareness exercise for advanced ESL learners.